The prevalence of lower urinary tract symptoms in Caesarean section patients’ first and seventh day of postpartum - Austin Julian; Johannes C. Prihadi; Yuma S. S. Indrajaya (Indonesian Journal of Obstetrics and Gynecology, 2023)
Objective: To compare the prevalence of Lower Urinary Tract Symptoms (LUTS) on the first day and the seventh day postpartum in Caesarian section patient